Effects of Acceptance and Commitment Therapy and Repetitive Transcranial Magnetic Stimulation on Obsessive–Compulsive Disorder - Zou, Jingzhi; Wu, Siliang; Yuan, Xin; Hu, Zhizhong; Tang, Jun; Hu, Maorong (Frontiers in Psychiatry, 2022)
Objective: This study aims to explore the difference of clinical efficacy and psychological flexibility of sertraline hydrochloride combined with acceptance and commitment therapy (ACT) or repeated transcranial magnetic stimulation (rTMS) in patients with obsessive–compulsive disorder (OCD). Materials and Methods: Sixty-three inpatients diagnosed with OCD were randomly divided into ACT group (N=32) and rTMS group (N=31), both of which were combined with sertraline hydrochloride. The following assessments were completed by the Hamilton Depression Scale (HAMD), Hamilton Anxiety Scale (HAMA), Yale–Brown Obsessive Compulsive Scale (Y-BOCS), Symptom Checklist 90 (SCL-90), Acceptance and Action Questionnaire (AAQ-Ⅱ), and Cognitive Fusion Questionnaire(CFQ) during pretreatment, 4 weeks posttreatment, and 8-week follow-up. Results: After treatment: (1) the SCL-90 score of two groups significantly decreased from pretreatment to 8-week follow-up (P<0.01 and P<0.001); (2) The HAMA, HAMD, and Y-BOCS scores of the two groups significantly decreased from pretreatment to 8-week follow-up (P<0.001 and P<0.05); (3) No statistically significant difference of the SCL-90, HAMA, HAMD and Y-BOCS between two groups; (4) The AAQ-Ⅱ and CFQ scores of the ACT group significantly decreased from 4 weeks posttreatment to 8-week follow-up (P<0.01). However, no statistically significant difference was observed in the rTMS group (P>0.05). Conclusions: Overall, our study suggested that sertraline hydrochloride combined with ACT or rTMS can improve the obsessive–compulsive symptoms, anxiety, and depression and has equivalent efficacy. Moreover, ACT can more effectively and durably improve the psychological flexibility of patients compared with rTMS.